Masters of Indian contemporary art - Sinha, Gayatri (Palette Art Gallery, 2005)
Catalog of a group exhibition of Indaian painters held from October 13-29, 2005 at Palette Art Gallery, New Delhi, India; photographic reproductions of their works and brief articles on their art.